Tribology of WC reinforced SiC ceramics: Influence of counterbody - Sandan Kumar Sharma; B. Venkata Manoj Kumar; Young-Wook Kim (Friction)
Abstract Hot pressed silicon carbide (SiC) composites prepared with 0, 10, 30 or 50 wt% tungsten carbide (WC) are subjected to dry sliding wear against WC-Co and steel ball. In particular an attempt has been made to answer the following important questions: (i) How does the load (from 5 to 20 N) effect sliding wear behaviour of SiC-ceramics against WC-Co and steel counterbodies? (ii) Is there any effect of WC content on friction and wear characteristics of SiC ceramics? (iii) Does the dominant material removal mechanism of SiC ceramics change with the addition of WC or counterbody? (iv) What is the influence of mechanical properties on the sliding wear? Experimental results indicated that coefficient of friction (COF) for the SiC ceramics varied between 0.66 and 0.33 with change in load and counterbodies. Wear volume for SiC ceramics found approximately 6−10 times more against WC-Co as compared against steel. Wear volume changes from 2.0 × 10–3 mm3 to 1.2 × 10–2 mm3 with change in counterbodies for SiC-(10, 30 or 50 wt%) WC composite at 20 N. SiC ceramics indicated abrasion and composites reveal tribochemical wear as major material removal mechanisms. Wear is influenced by the hardness of counterbody and fracture toughness of SiC-WC composites.